BRIDGING THE GAP: NEEDS OF CORRECTIONAL EDUCATIONAL FACILITIES FOR WOMEN PRISONERS IN INDIA - Singh, Riti; Lone, Ahrar Ahmad (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The effective role of prison education is becoming increasingly crucial as more prisons are constructed and the prison population rises in parallel. Prison education aims to address the problems associated with correctional facilities, emphasizing the role of education in this setting and its effects on the formation of human personalities. Education helps to shape a person’s lifestyle. The paper is based on an analysis of various research articles that aim for in-depth exploration of the complexities and objectives of prison education, including reducing recidivism, offering professional training, and calming them down. The article offers in-depth information about the detrimental effects of education programs on a person’s personality development. The study addresses the effects of prison education on personality development and recidivism, as well as its capacity to transfer information and skills. The research shows the benefits and need for effective prison education and the need for effective correctional educational facilities for women prisoners in India. The study shows the effect of correctional educational facilities on reducing recidivism rates by equipping prisoners with the skills necessary to obtain work.